Physico-chemical characterization of oils extracted from noni, spinach, ladys finger, bitter gourd and mustard seeds, and copra - Lee, S. T.; Radu, Son; Ariffin, Abdul Azis; Mohd Ghazali, Hasanah (Taylor & Francis, 2015)
The physico-chemical properties of solvent-extracted oil from the seeds of noni (Morinda citrifolia L.), spinach (Spinacia oleracea L.), lady’s finger (Abelmoschus esculentus (L.) Moench), bitter gourd (Momordica charantia L.), mustard (Brassica nigra (L.) Koch), and the dried kernel (copra) of coconut (Cocos nucifera L.) were characterized. Among these sources, spinach seed had the lowest oil content (4.5 ± 0.4%) while coconut kernel had the highest oil content (63.1 ± 2.8%). Palmitic, oleic, and linoleic acids were the major fatty acids for spinach, lady’s finger and noni seed oils, while erucic, eleostearic, and lauric acids were the major fatty acids for mustard seed oil, bitter gourd seed oil, and coconut kernel oil, respectively. All of the oils possessed at least three major peaks in their triacylglycerol profiles except for bitter gourd seed oil which had only one major peak (1-stearoyl, 2,3-dieleostearoyl). The last endothermic peaks were –12.4, –6.0, 6.8, 57.7, 2.7, and 24.3ºC for noni, spinach, lady’s finger, bitter gourd and mustard seed oils, and coconut oil, respectively. Initially, the solid fat content of bitter gourd seed oil decreased gradually, but became rapidly after 50 until 60ºC. Coconut oil had its solid fat content reduced rapidly around 14 to 28ºC.